PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI MASALAH EKONOMI DALAM SISTEM EKONOMI DI KELAS X-TKJ SMK NEGERI 1 FANAYAMA - Sarumaha, Herlinawati (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
This research aims to enhance the activity, interest, and learning outcomes of tenth-grade students at SMK Negeri 1 Fanayama in the subject of economics after participating in Problem-Based Learning (PBL). This study employed a Classroom Action Research (CAR) conducted in two cycles, each comprising three sessions. The research was conducted in the tenth-grade classrooms of SMK Negeri 1 Fanayama. Data collection techniques included tests, observations, and questionnaires, while data analysis utilized quantitative descriptive analysis. Test techniques were employed to measure student learning outcomes, observations were carried out to assess student activity during learning sessions, and questionnaires were used to gauge student interest in learning while participating in PBL sessions. The findings revealed an improvement in learning mastery, learning interest, and learning activity from the initial stage to the second cycle. The learning outcomes in the second cycle reached the predetermined success indicator, with learning outcomes in the second cycle increasing to 100% from 89% in the first cycle, while student interest in the first cycle, at 89%, increased to 100% in the second cycle, and student learning activity at 100% in the first cycle increased to 100% in the second cycle. These improvements indicate the success of implementing the PBL learning model. Thus, it can be concluded that the enhancement of students' economics learning activity, interest, and outcomes through the PBL learning model has been successfully achieved.